2019
DOI: 10.1007/s40090-019-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and DFT studies of the removal of pharmaceutical metronidazole from water using polypyrrole

Abstract: The polypyrrole (PPy) was used as an adsorbent material for efficient removal of pharmaceutical metronidazole from aqueous solutions. The physiochemical parameters influencing the adsorption process such as adsorbent dose, temperature, pH, initial concentration and contact time were systematically investigated. The optimum adsorption efficiency is achieved at pH 6.17 after 120 min of contact time. In addition, the Langmuir isotherm and pseudo-second-order models were found to explain the metronidazole adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…5g). 40–74 In addition, rGOFpl foam was used to purify the aqueous solution containing the artificial dye Rhodamine B. It was found that the UV vis characteristic peak of Rhodamine B in condensed and collected water at 570 nm disappeared after purification, and the purification efficiency was close to 100% with the color of the solution changing from pink to colorless, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5g). 40–74 In addition, rGOFpl foam was used to purify the aqueous solution containing the artificial dye Rhodamine B. It was found that the UV vis characteristic peak of Rhodamine B in condensed and collected water at 570 nm disappeared after purification, and the purification efficiency was close to 100% with the color of the solution changing from pink to colorless, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Absorbing materials, i.e., graphene oxide (pyrene, GO-1 and coronene-based, GO-2) and chitosan were simulated as dimers due to the high computational cost of modelling polymeric structures. Nevertheless, several works have represented these types of compounds in these forms [ 41 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…The adsorption experiments were conducted in 150 mL Erlenmeyer flasks containing 50 mL of adsorbate solution with a constant agitation speed of 150 rpm. The adsorption tests of sodium salicylate on the wood sawdust were performed at different experimental conditions such as initial pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), solid/liquid contact time (0-300 min), adsorbent dosage (0.1-1.5 g/L), temperature (25-50°C) and initial concentration (10-200 mg/L). The initial solution pH was adjusted to the desired values by the addition of HCl (0.1 M) or NaOH (0.1 M) solutions.…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…Various wastewater decontamination technologies such as photocatalytic degradation [5][6][7][8] , reduction 9 , electrocoagulation 10 , and adsorption [11][12][13][14] . Among these techniques, the adsorption was considered as one of the most promising methods for the removal of pollutants from aqueous solutions because of its flexibility, low-cost, high efficiency and operational simplicity [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%